EVALUASI TEKNIS STRUKTUR RUMAH PANGGUNG TOMBASIAN MINAHASA TERHADAP BEBAN GEMPA SESUAI DENGAN STANDAR NASIONAL INDONESIA (SNI) 1726-2019 - Amalia Nurhajayanti Tawary; Djoni Agustaf; Nicky Rampengan (UKI Press, 2025)
The Tombasian stage house uses cempaka wood, and during an earthquake the Tombasian stage house will shift slightly without damage to its parts. The purpose of this study is to analyze how the behavior of the Tombasian stage house structure against earthquake loads, so that whether it can be said that the Tombasian stage house structure meets the requirements of strength and stability and meets the requirements in accordance with SNI 7973-2013. This research uses the ultimate value research method of structural analysis by analyzing the reaction of the structure to the working load and evaluating the strength of the structure. The analysis uses Structural Analysis Application software and Microsoft Excel. Earthquake load analysis using the dynamic spectrum response method. Cempaka wood material with a specific gravity of 530 kg/m3 and a modulus of elasticity of 8894.63 Mpa. The results of the ultimate internal forces from the structural analysis application show that the ultimate pressure is smaller than the nominal pressure calculated using the LRFD method. Buckling occurs when the ultimate pressure acts. The ultimate bending moment and ultimate shear force are less than the nominal bending moment and nominal shear force. And the deflection also complies, because it is smaller than the allowable deflection. So it can be said that all structural elements are declared safe, meet the requirements of strength and stability. Keywords: Stage house, structural evaluation, timber structure, earthquake force, spectrum response, LRFD